Use of synthetic peptides of influenza nucleoprotein to define epitopes recognized by class I-restricted cytotoxic T lymphocytes. - Bastin, J; Rothbard, J; Davey, J; Jones, I; Townsend, A (1987)
The conserved epitopes of influenza nucleoprotein (NP) recognized by class I MHC-restricted CTL from CBA (H-2k) and C57BL/10 (H-2b) mice have been defined in vitro with synthetic peptides 50-63 and 365-379, respectively. Two Db-restricted clones were described that recognize different epitopes on peptide 365-379. Finally, the recognition of complete NP was shown to be approximately 200-fold less efficient than peptide in the cytotoxicity assay. These phenomena are closely related to results with class II-restricted T cells and they strengthen the hypothesis that influenza proteins are degraded in the infected cell before recognition by class I-restricted CTL.